Characterization of adverse drug events identified by trigger in Brazilian pediatric inpatients - Lunara Teles Silva; Ana Carolina Figueiredo Modesto; Renato Rocha Martins; Flavio Marques Lopes (Brazilian Society of Pediatrics, 2020)
Objective: To describe the frequency and characteristics of adverse drug events in pediatric inpatients in a Brazilian tertiary teaching hospital. Methods: A cross‐sectional study was conducted by retrospective and manual chart review of 240 pediatric admissions to identify adverse drug events using 17 triggers. When triggers were detected in the chart, reviewers investigated the chart in depth to decide whether an event occurred. Consensus about the occurrence of the event was obtained in meeting with a healthcare team. Events were classified by harm category and drugs were classified according to the Anatomical Therapeutic Chemical Classification. Patients who had suffered were compared to those who had not experienced events using the chi‐squared test and the Mann-Whitney U test. Results: A total of 62 adverse events were found, and 18.8% of the patients had at least one event. Adverse events rates were 25.83 per 100 admissions, 20.27 per 1000 patient‐days, 25.94 per 1000 drugs, and 2.12 per 1000 drug doses. All events found were classified as temporary harm, and cardiovascular drugs were most frequently related to events. Groups of patients with and without event were segregated (p < 0.05) by the length of stay, number of drugs, and drug doses. Conclusion: The use of triggers demonstrated its utility in a pediatric setting by identifying harm. Adverse events rates were found to be higher than those of previous studies, but the harm rate was lower than other studies. This study enables the measurement of adverse events in order to define strategies to mitigate or reduce harm. Resumo: Objetivo: Descrever a frequência e as características dos eventos adversos a medicamentos em pacientes pediátricos internados em um hospital universitário terciário brasileiro. Métodos: Foi realizado um estudo transversal por meio da análise retrospectiva e manual de prontuários de 240 internações pediátricas para identificar eventos adversos a medicamentos utilizando 17 rastreadores. Quando foram identificados rastreadores no prontuário, os analistas investigaram extensivamente o prontuário para decidir a respeito da existência de um evento. O consenso sobre a ocorrência do evento foi obtido em reunião com uma equipe de profissionais da saúde. Os eventos foram classificados por categoria de dano e os medicamentos foram classificados de acordo com a Classificação Anatômica Terapêutico‐Química. Os pacientes que sofreram eventos adventos foram comparados aos que não apresentaram eventos adversos, com o teste qui‐quadrado e o teste U de Mann‐Whitney. Resultados: Verificou-se um total de 62 eventos adversos e 18,8% dos pacientes apresentaram ao menos evento. As taxas de eventos adversos foram de 25,83 por 100 internações, 20,27 por 1.000 pacientes/dia, 25,94 por 1.000 medicamentos e 2,12 por 1.000 doses de medicamentos. Todos os eventos encontrados foram classificados como dano temporário e os medicamentos cardiovasculares foram frequentemente associados aos eventos. Grupos de pacientes com e sem eventos apresentaram diferenças (p < 0,05) em relação ao tempo de internação, número e doses de medicamentos. Conclusão: O uso de rastreadores demonstrou sua utilidade no contexto pediátrico ao identificar danos. As taxas de eventos adversos foram maiores do que as taxas de estudos anteriores, porém a categoria de dano foi menor que em outros estudos. Este estudo possibilita a medição dos eventos adversos a fim de definir estratégias para minimizar ou reduzir os danos.